ANALYTE SENSORS AND SYSTEMS INCLUDING RETENTION TAB AND METHODS OF MANUFACTURING SAME - CHARLTON STEVEN C (2016)
In some aspects, an analyte sensor is provided for detecting an analyte concentration level in a biological fluid sample. The analyte sensor has a base including a top and bottom side, a lid, and an attachment member including one or more retention tabs coupled proximate the top side so that the analyte sensor can be grasped by the sensor's top side. Manufacturing methods and systems adapted to use and dispense the analyte sensors are provided, as are numerous other aspects.